Palaeolimnology of the Santa Clara Abajo Formation, Triassic of the Cuyana Basin Argentina, inferred from fish taphonomy - Benavente, Cecilia Andrea (2021)
The Santa Clara Abajo Formation in the north of Mendoza Province, Argentina, is part of the Triassic Cuyana rift Basin infill and consists of fluvial, deltaic and lacustrine units. The combination of progradational to aggradational stacking pattern plus the identification of a fluctuating profundal facies association suggests the Santa Clara Abajo palaeolake was a balanced-fill lake system. Lake-centre sediments (finely laminated mudrock facies) preserve pseudobeaconiid actinopterygian fish represented primarily by bones and scales, generally undeformed and concordant with bedding planes. We propose that variation of articulation degree of these fish combined with sediment features provides insights into palaeolimnological changes in this single lake system over time, primarily water temperature. The fish fossils are sorted into three taphonomic modes: Mode A, isolated and dispersed scales; Mode B, associated but dispersed scales, loosely to well sorted, and low to moderate density; and Mode C, scale patches and articulated fishes. We conclude these modes represent, respectively, warm, fluctuating warm–cold and cold water conditions. Stratigraphical analysis of the taphonomic modes for the balanced-fill lake model revealed an up-section pattern of fluctuating water temperatures (cold and warm), to a stable-cold pattern, to a stable-warm pattern and to fluctuating thermal conditions (cold and warm) again. This pattern is linked to lake-level fluctuations resulting in lacustrine intervals that reflect hydrological closure to opening to closure again.